(untitled) (Research, Society and Development, 2020)
The objective of this study was to determine the effect of dietary calcium levels on productive and reproductive traits of European male quail (Coturnix coturnix). A total of 60 European male quail, at 35 days of age, weighing 248.9g ± 8.1g were distributed in a completely randomized experimental design with five calcium levels (1.5, 2.0, 2.5, 3.0 and 3.5%), and 12 replicates per treatment (one bird each replicate). The experimental period was 35 to 70 days of age. At 70 days of age, the parameters of male productive traits assessed were: feed consumption, calcium consumption, weight gain and body weight of birds. The reproductive traits analyzed were: hatchability and fertility of eggs. Early, intermediate and late embryonic mortality were also evaluated. The diet containing 3.16% of calcium provides higher percentage of hatched eggs and did not show a negative effect on productive performance of European quails.